2019
DOI: 10.26650/ibr.2019.48.0027
|View full text |Cite
|
Sign up to set email alerts
|

İşyerinde Etik Algısı Cinsiyete ve Kuşaklara Göre Değişir mi? Türkiye’deki Çalışanlar Üzerine Ampirik Bir Çalışma

Abstract: ÖzÇalışanların etik dışı davranışları örgütte yarattığı ciddi olumsuz sonuçlar nedeniyle incelenmesi gereken önemli bir konudur. Ancak çalışanların davranışlarına yansıyan etik algılarını anlamak ve yönetmek oldukça karmaşık bir konudur. Etik algısını anlama çabasının geniş bağlamda ele almasının gerekliliği göz önüne alınarak bu çalışmanın amacı işyerinde etik algısının cinsiyete ve kuşaklara göre farklılıklarının tespit edilmesidir. Türkiye'de Y kuşağından 460, X kuşağından 256 ve bebek patlaması kuşağından … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…He found an absolute difference between the two groups in terms of work ethics and stated that individuals born before 1980 had higher scores on ethics. Yıldız and Yakut (2019) also stated in their study that BBers and GenX tend to behave more ethically than GenY in Turkey [104]. On the other hand Jobe (2014) [47] found that there was a difference in intergenerational work ethics in their study and stated that the GenY had higher business ethics values than the GenX and BBers [109].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 90%
“…He found an absolute difference between the two groups in terms of work ethics and stated that individuals born before 1980 had higher scores on ethics. Yıldız and Yakut (2019) also stated in their study that BBers and GenX tend to behave more ethically than GenY in Turkey [104]. On the other hand Jobe (2014) [47] found that there was a difference in intergenerational work ethics in their study and stated that the GenY had higher business ethics values than the GenX and BBers [109].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 90%
“…This categorization was made by taking into account different generations. In determining the generations, the most widely accepted generations (Yıldız and Giray Yakut, 2019;Weber and Urick, 2017;Zemke, Raines and Filipczak, 2013;Costanza, Badger, Fraser, Severt and Gade, 2012) were taken into account.…”
Section: Data Set and Variablesmentioning
confidence: 99%
“…Dolayısıyla, bireylerin etik olan ile olmayanı nasıl değerlendirdikleri önem kazanmaktadır. Etik algıya ilişkin değerlendirmeler bireysel, örgütsel ve toplumsal düzeyde farklılıklar gösterdiği gibi, kuşaklar arasında da önemli farklar gösterebilmektedir (Yıldız ve Giray Yakut 2019). Etik algı üzerindeki bir diğer etmen ise cinsiyettir.…”
Section: Etik Algıda Cinsiyete Göre Farklılıklarunclassified